Conflicting Demands of Chemistry and Inclusive Teaching-A Video-Based Case Study - Simone Abels; Brigitte Koliander; Thomas Plotz (MDPI AG, 2020)
Almost every country in the world is obligated to implement education policies to enable an inclusive school system. However, implementing techniques to be inclusive in schools is a major challenge to teachers, especially to those teaching a subject at secondary level and higher. Most of the literature concerning inclusive science education was published in recent years, and is more normative than empirical. Teachers struggle to transfer these normative demands to their accustomed way of teaching science. In this study, we analyze conflicts a teacher experiences when teaching a so-called ‘hard science’ like chemistry at an inclusive school. On the one hand, inclusive science education should facilitate participation in science specific learning processes for all learners. This broad perspective on inclusion demands that everyone can take part in everyday classroom life. On the other hand, chemistry strives for the understanding of abstract concepts, theories and models, which forms a barrier to learning chemistry for many people. This paper presents an explorative case study focusing on these conflicting demands. To reconstruct the inconsistencies, we analyzed a videotaped teacher−student discourse on atoms. Using the documentary method, a qualitative approach developed by the sociologist Ralf Bohnsack [1] distinguishing between explicit and implicit knowledge, it was possible to reveal the orientational frameworks guiding the teacher’s actions. On the surface level, traditional scientific educational approaches structure the discourse. Reconstruction of the discourse is deep, as evidence was found for a participation-oriented framework as well as for the challenges the conflicting demands of chemistry and inclusive teaching put on teaching. We implicate that future professional development courses must not only concentrate on combining chemistry with inclusive pedagogies, i.e., how to teach, but also on the reflection of implicit beliefs concerning inclusive chemistry teaching.